Advocating evidence based health promotion in physiotherapy - J.M. Frantz (AOSIS, 2008)
There has been a significant acceleration in the development ofhealth promotion in Africa over the last 20 years. Health promotion is a practicalapproach to achieving greater equity in health. It has thus become an essentialcomponent of health delivery for all health professionals. Health promotionstrategies can develop and change lifestyles as well as have an impact on thesocial, economic and environmental conditions that determine health. The mostvisible challenge for health promotion development in Africa is the fact that people only passively participate in thehealth promotion process. Health professionals such as doctors and nurse control the majority of the programmes andthe question remains: "What is the role of Physiotherapy in health promotion?" This paper thus aims to highlight andrecommend the role of Physiotherapy in evidence-based health promotion